Covid-19, Global Crisis and the Challenges of Human Security Management in Nigeria - Oluka, Nduka Lucas (Universitas Negeri Semarang, 2022)
As Nigeria reels under the security challenges causes by the insurgency of the Boko Haram Islamic sect, and Islamic State West African Province, ISWAP in the North East region, as well as banditry, armed robbery, kidnappings for ransom, ritual killings, separatist movement of the Indigenous People of Biafra, IPOB and the menace of the Fulani Herdsmen, the unprecedented killer COVID-19 pandemic and its concomitant global crisis changed the pattern of the security challenges and greatly undermined human security in the country. It is within this premise that this study made concerted effort to review the changing pattern of the Nigeria’s public safety and national security challenges in the COVID-19 pandemic era which in turn undermined human security. To achieve its objectives, this study adopted the historical research design which is qualitative and explorative in nature. Thus, secondary sources of data were reliably used in gathering of materials for the study and for gleaning extant literatures in the study area. Because of its contribution to the development of a civil society which is largely in practice in recent times, the Natural State theory was adopted as its theoretical framework. The study finds out among others that in the face of the outbreak of Coronavirus (COVID-19) pandemic, its accompaniment global crisis and the existing national security challenges in Nigeria are on the increase rather than in the decrease and all of which in turn threatened human security that was already in comatose state. Study concludes that the nexus between the security challenges in the pre-COVID-19 and COVID-19 pandemic eras is that both have tolled on human and material capital in Nigeria. The study therefore offers useful policy options to these national issues.